Carbon-water flux coupling under progressive drought - Boese, Sven (2020)
Water-use efficiency (WUE), defined as the ratio of carbon assimilation over evapotranspiration (ET), is a key metric to assess ecosystem functioning in response to environmental conditions. It remains unclear which factors control this ratio during periods of extended water limitation. Here, we used dry-down events occurring at eddy-covariance flux tower sites in the FLUXNET database as natural experiments to assess if and how decreasing soil-water availability modifies WUE at ecosystem scale. WUE models were evaluated by their performance to predict ET from both the gross primary productivity (GPP), which characterizes carbon assimilation at ecosystem scale, and environmental variables. We first compared two water-use efficiency models: the first was based on the concept of a constant underlying water-use efficiency, and the second augmented the first with a previously detected direct influence of radiation on transpiration. Both models predicting ET strictly from atmospheric covariates failed to reproduce observed ET dynamics for these periods, as they did not explicitly account for the effect of soil-water limitation. We demonstrate that an ET-attenuating soil-water-availability factor in junction with the additional radiation term was necessary to accurately predict ET flux magnitudes and dry-down lengths of these water-limited periods. In an analysis of the attenuation of ET for the 31 included FLUXNET sites, up to 50 % of the observed decline in ET was due to the soil-water-availability effect we identified in this study. We conclude by noting that the rates of ET decline differ significantly between sites with different vegetation and climate types and discuss the dependency of this rate on the variability of seasonal dryness.